Computational Bibliometric Analysis on Publication of Techno-Economic Education - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2022)
Techno-economics involves the systematic evaluation of economic aspects to provide solutions to technical problems encountered. The study of techno-economic analysis can provide a basis for decision-making related to economic factors. This study was to analyze the scope of research on techno-economic education using bibliometric evaluation and data mapping approach (i.e., VOSviewer software). Material research data was gathered from application reference manager databases. The study material titles, keywords, and abstracts are used to guide the search process. In the period 2017-2022, the analysis was conducted using the number of publications collected, which totaled 288 related papers. Based on the number of publications related to techno-economic educations, the total publications from 2017-2022 are unstable. However, in 2021 publications related to techno-economic education have increased. This study highlights the value of bibliometric analysis in providing information on how phenomena occur. This study is meant to assist and serve as a reference for researchers undertaking and deciding on research topics.